Towards Safer Seafood: What Indonesian Law Should “Say” about Mercury-Contaminated Fish - Quina, Margaretha (UI Scholars Hub, 2016)
Fish is a popular culinary dish in Indonesian culture and a major economic resource on which many people depend their livelihood. However, with severe pollution in Indonesian water, including uncontrolled mercury pollution which persists in the food chain and eventually gets into humans’ body as the top predator, fish safety is particularly worrying – especially taking into account the frequency of average Indonesians’ consumption of fish. In various jurisdictions, the management tool used by lawmakers and regulators with regard to this issue is information disclosure, or known as “fish advisory warning,” to cover the failure of command and control. This paper analyses whether Indonesian laws have provided the mandate or authority to issue fish advisory warning under Fishery Law, Food Law, Environmental Protection and Management Law, and Public Information Disclosure Law. It concluded that Indonesian law implies a statutory mandate for the government to issue fish advisory warning, at least in a situation involving the threat to general life – not specifically through the Fishery Law, Food Law, or EPML, but through PIDL’s immediate information mandate.